2020
DOI: 10.1177/0271678x20954015
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of cerebrovascular reactivity in response to hypercapnic challenge in a mouse model of repetitive mild traumatic brain injury

Abstract: Incidences of repetitive mild TBI (r-mTBI), like those sustained by contact sports athletes and military personnel, are thought to be a risk factor for development of neurodegenerative disorders. Those suffering from chronic TBI-related illness demonstrate deficits in cerebrovascular reactivity (CVR), the ability of the cerebral vasculature to respond to a vasoactive stimulus. CVR is thus an important measure of traumatic cerebral vascular injury (TCVI), and a possible in vivo endophenotype of TBI-related neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 108 publications
3
15
0
Order By: Relevance
“…Similarly, in human AD microvessel extracts, it was found that reduced brain mural cell levels correlated with cognitive impairment and AD diagnosis ( Bourassa et al, 2020 ). In our prior work using this r-mTBI mouse model, we observed a decline in cognitive performance at 1 month post-injury which progressively deteriorated at 3 and 6 months post-injury ( Lynch et al, 2016 ; Lynch et al, 2020 ), in line with the mural cell degeneration we observed at these time points following r-mTBI in the current studies, though further work is needed to understand the potential correlation between brain mural cell changes and cognitive function. Collectively, these studies point toward mural cell disruption as a contributing factor in TBI pathogenesis and cognitive impairment.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Similarly, in human AD microvessel extracts, it was found that reduced brain mural cell levels correlated with cognitive impairment and AD diagnosis ( Bourassa et al, 2020 ). In our prior work using this r-mTBI mouse model, we observed a decline in cognitive performance at 1 month post-injury which progressively deteriorated at 3 and 6 months post-injury ( Lynch et al, 2016 ; Lynch et al, 2020 ), in line with the mural cell degeneration we observed at these time points following r-mTBI in the current studies, though further work is needed to understand the potential correlation between brain mural cell changes and cognitive function. Collectively, these studies point toward mural cell disruption as a contributing factor in TBI pathogenesis and cognitive impairment.…”
Section: Discussionsupporting
confidence: 81%
“…In our studies, we performed flow cytometry to assess the state of the mural cell population after r-mTBI and found no change in the of number of CD13+ cells between r-sham and r-mTBI cerebrovessels at 6 months post-injury. Furthermore, we recently reported no difference in mural cell vessel density between r-sham and r-mTBI animals (up to 9 months post-injury) based on CD13 vessel coverage using confocal microscopy ( Lynch et al, 2020 ). Thus, while mural cell loss may occur acutely following brain trauma ( Choi et al, 2016 ; Bhowmick et al, 2019 ), there does not appear to be an overt reduction in the number of mural cells in the chronic phase post-injury, but rather a progressive decline in key mural cell proteins (i.e., PDGFRβ and αSMC-actin), which are expressed in both pericytes and smooth muscle cells ( Alarcon-Martinez et al, 2018 ; Hellstrom et al, 1999 ; Skalli et al, 1989 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a chronic repetitive mTBI model in mice, involving two mTBIs per week for three months, a study demonstrated a significant reduction in CBF at three months post last injury 78 . Using the same injury paradigm, differences in compromised cerebrovascular reactivity were demonstrated at 3 and 9 months post-last injury 79 , reflecting findings in a human moderate to severe TBI patient population 80 . BBB disruption has also recently been shown after mTBI in swine, with the same appearance, albeit to a much lesser extent as found in moderate to severe TBI in humans, although the rete mirabile in swine may limit applicability to human TBI 58,73 .…”
Section: Vascular Injurysupporting
confidence: 56%
“…Preclinical CVR studies predominantly follow similar approaches to human studies but involve additional considerations such as the effect of anaesthetic agents on resting CBF (Stringer et al, 2021). Isolated vessel preparations (Seitz et al, 2004;Joutel et al, 2010), laser speckle imaging (Lynch et al, 2020), and multiphoton microscopy (Joo et al, 2017;Kisler et al, 2017) can also assess CVR preclinically and may help improve understanding of how impaired vasoreactivity develops and further direct validation of CVR-MRI as a clinical biomarker of cerebrovascular health (Stringer et al, 2021). CVR measurements using MRI techniques showed lower repeatability between-days than within-days (Dengel et al, 2017;Merola et al, 2018).…”
Section: Validationmentioning
confidence: 99%